Integration of neural models in the process of technological preparation of the production of castings - I. B. Odarchenko; V. A. Zharanov; I. N. Prusenko (Литьë и металлургия)
The methodical application of neural network modeling in preparation and optimization of casting technology is described. A new technique for classifying castings based on geometric relationships of the geometry of parts and information on the distribution of wall thickness in castings.